zumjhoo

zumjhoo

Lv5

Indian Institute of Technology - IIT Palakkad

0 Followers
0 Following
0 Helped
Physicist.

ANSWERS

Published106

Subjects

Algebra71Calculus3Physics31Economics1
Answer:1 ) we know the slope-intercept form of a straight line is y = mx+c. Fr...
1) let 2) let 3) let 4) let
Answer: For infinite solution rank of the matrix should be less than the no. o...
Answer: Please see the attachment below
Answer: If ax3+bx2+cx+d=0 then By putting values in a,b,c, and d we will get t...
Answer: If ax3+bx2+cx+d=0 then By putting values in a,b,c, and d we will get t...
Answer: x = 2,3
Answer: 1) 1 + 5 x + 10 x^2 + 10 x^3 + 5 x^4 + x^5 2) -1 + 5 x - 10 x^2 + 10 x...
Answer: density = mass/ volume = m/V
Answer:
Answer: 3*1 + 10/7 = 31/7 = 4.428
Answer: r = 1- a/s
Answer: Invalid equation. Both sides are p present which cancels each other an...
Answer: y = 3, 6
Answer: n(n-1)(n-2)
Answer: q = -1, or 3
Answer: Please see the attachment below
Answer:
Answer: y = 1.5x + 2.7
Answer: y = 0.5x +1.5
Answer:
Answer: a) 2 - t - 2 t^2 + t^3 b) Inverse won't exist for the root of the firs...
Answer:
Answer: x = 5
Answer: Given Q + P =10 Q + 2P = 12 On solving these equations P = 2 and Q = 8
Answer: Mount Everest
Answer: Mount Everest
Answer: Th rate of change of y with respect to x is
Answer: Equation of straight line passing through two points (x1,y1), (x2,y2) ...
Answer: common multiple = 4w^7x^3
Answer: Given p= 0.4q p/0.4 = q q = 2.5p q is 250% of p
Answer: L.H.S.
Answer: It's the algebraic identity (q-m)(q+m) = q^2 - m^2
Answer: Put the value of u and t and solve tu + u = -0.78
Answer: n = 1.41667
Answer: x = -1 y = 3
Answer:
Solve the system of equations.
 
x+4 y-z=14 
x+5 y+z=27 
x-4 y+5 z=-2
 
Select the correct choice below and fill in any answer boxes within your choice.
A. The one solution is x = ___, y = ___, and z =___. (Simplify your answers.)
B. There are infinitely many solutions. If z is allowed to be any real number, then x =___ and y = ___ (Type expressions using z as the variable.)
C. There is no solution.
 
View an example I All parts showing
Solve the system of equations.
 
x+6 y-z=-19 
x+7 y+z=-18 
x-5 y+7 z=30
 
Use the left-to-right elimination method to solve this system of equations. This method reduces the system to an equivalent system in echelon form shown below, where a, b, c, d, e, and f are constants.
 
x + a y + bz = d 
         y + cz = e 
                 z = f
 
Note that the first equation, x + 6y - z = -19, is already in the form of the first row in echelon form.
 
The operations shown helom when perisemed on a system of equations, result in an equivalent system
1. Interchange any two equations.
2. Multiply both sides of the equations by the same nonzero number.
3. Multiply any equation by a rumber, add the result to a second equation, and then replace the second equation with the sum.
 
To eliminate the x-term from the second equation, multiply both sides of the first equation by -1 and ass the result to the second equation.
 
 
 
 
Now use the same method to eirinale the x-term in the third equation.
Multely beth sides of the first equation by -1 and add the result to the third equation.
 
 
The equation system with the nea second and third equation is shown below. The next step is to eliminate the yeterm from the thad equation.
 
x + 6y - z = 19 
      y + 2z = 1 
-11y + 8z = 49
 
To eliminate the y-term in the third equation, multiply both sides of the second equation by 11 and add the result to the third equation.
 
 
Finally, to obtain an x-coefficient of 1 in the third equation, multiply both sides of the third equation by .
 
 
The system is now in echelon form. Solve by back-substitution.
x + 6y - z = -19 
        y + 2z = 1 
                z = 2
 
The third equation gives the value of z.
Back-substitute 2 for z in the second equation and solve for y.
 
y + 2(2) = 1 
y = -3
 
Finally, back-substitute the values of y and z in the first equation and solve for x.
 
             x + 6 (-3) - (2) = -19 
                      x = 1    
 
Therefore, the solution to the given system is as shown below.
          x = 1               y = -3              z = 2
Answer: x = -2, y = 5, z = 4
Answer: Just put (x+h) at the place of x for f(x+h) and solve
Answer: 8) 9 9) -3 10) 12

Weekly leaderboard

Start filling in the gaps now
Log in